(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: To do a research study on Medicolegal Autopsies conducted at Government Medical College Mortuary, Ongole, Andhra Pradesh from 1st January 2020 to 31st December 2020. Materials & Methodology: This study was conducted at Government Medical College, Ongole from 1st January to 31st December 2020. A total of 534 medicolegal cases were brought to mortuary for the sake of medicolegal autopsy during the study period. Result: In the research study, it is evident from the statistics that maximum number of medicolegal autopsies were conducted in the decreasing order in the following deaths - Road Traffic Accidents < Poisoning < Hanging < Homicidal Deaths < Deaths due to hit by Train < Drowning < Burns < Fall from Height < Snake Bite. Medicolegal autopsies were done more in males compared to females in almost all types of deaths. Likewise maximum number of autopsies were conducted in the active age group of 18 to 36 years